2010
DOI: 10.1089/gtmb.2010.0078
|View full text |Cite
|
Sign up to set email alerts
|

A Genomic Insight into the Peopling of Manipur, India

Abstract: this study provides evidence for the genetic heterogeneity of the Manipur populations. It also supports the hypothesis, based on the archeological and linguistic findings, that the northeastern populations of India have a close genetic affinity with the southeastern and East Asian populations. The genetic discontinuity observed between the studied populations and the other non-Northeast Indian populations suggests the role of northeast border as a "barrier" rather than a corridor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The high degree of genetic differentiation (5.2%) in these populations could be suggestive of their different origin of these populations maintaining its own gene pool without the possibility of gene flow, following strict endogamous nature which is further supported by AMOVA analysis which indicates that the highest percentage of among group variance is seen between Naga and Kuki groups (7.09%) as compared to interpopulation variation among the groups (0.31%). When the four presently studied populations and the earlier studied populations from Manipur (Saraswathy et al 2009a;Saraswathy et al 2009b;Meitei et al 2010;Kameih et al 2018;Kshatriya et al 2019) are considered jointly on the basis of five markers, the GST value was 4.6%, which may be attributable to variation among the populations of Manipur.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…The high degree of genetic differentiation (5.2%) in these populations could be suggestive of their different origin of these populations maintaining its own gene pool without the possibility of gene flow, following strict endogamous nature which is further supported by AMOVA analysis which indicates that the highest percentage of among group variance is seen between Naga and Kuki groups (7.09%) as compared to interpopulation variation among the groups (0.31%). When the four presently studied populations and the earlier studied populations from Manipur (Saraswathy et al 2009a;Saraswathy et al 2009b;Meitei et al 2010;Kameih et al 2018;Kshatriya et al 2019) are considered jointly on the basis of five markers, the GST value was 4.6%, which may be attributable to variation among the populations of Manipur.…”
Section: Discussionmentioning
confidence: 83%
“…6.70% on the basis of 24 autosomal DNA markers. Meitei et al (2010) conducted a study among population groups of Manipur using 7 alu InDel markers and found higher GST value among tribal populations (7.4%) than non-tribal populations (2.2%) and it reveals that the diversity within the tribal groups is higher when compared with non-tribal. The high degree of genetic differentiation (5.2%) in these populations could be suggestive of their different origin of these populations maintaining its own gene pool without the possibility of gene flow, following strict endogamous nature which is further supported by AMOVA analysis which indicates that the highest percentage of among group variance is seen between Naga and Kuki groups (7.09%) as compared to interpopulation variation among the groups (0.31%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations